Praktek Pembayaran Angsuran Kredit Jual Beli Sepeda Motor - Zul Azimi (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
Credit installments are installments that are deferred payments orpayments on a pending basis, by providing installments in certainamounts for a certain amount of time, the price is more expensivethan the cash price. This study aims to determine the practice ofpaying installments for motorcycle buying and selling loans at PT.Mandala Sigli. This type of research is field research usingdescriptive methods of analysis. The data collection usesobservation, interview, and observation techniques. The results of thestudy showed the practice of paying installments for motorcyclebuying and selling loans at PT. Mandala Sigli is carried out with adaily payment technique in accordance with the agreement, thelength of installments determines the length of payment, and thebenefits obtained by the company will be different. Installmentpayment of motorcycle buying and selling credit at PT. Mandala Sigliaccording to the view of Islamic law is not appropriate, this isbecause there is an element of fine in case of delay which is forbiddenin Islam, and is included in the riba jahiliyah (usury nasi'ah), whichis an addition to the debt that arises due to the delay factor